2000
DOI: 10.1002/1097-010x(20001101)287:6<440::aid-jez5>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin on dopamine metabolism in the hypothalamus and the pituitary of the rainbow trout, Oncorhynchus mykiss

Abstract: The present paper discusses the effect of a single melatonin treatment (0.5 mg/kg, i.p.) on the dopaminergic metabolism in the hypothalamus and pituitary of the rainbow trout. The effects of exogenous melatonin on dopamine (DA) and 3,4-dihydroxyphenylacetic acid (DOPAC) contents were compared with the variations in the content of these catecholamines associated to the natural increase in the endogenous melatonin from daytime (3 hr before lights off) to nighttime (3 hr after lights off). Animals treated with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, an earlier study in the same species reported that high melatonin doses did not affect DA turnover in the hypothalamus (106). In rainbow trout, melatonin inferred a decrease in the hypothalamic‐pituitary DA turnover (107), a supposed step by which melatonin modulated LH secretion, as indicated in a previous study (108). In carp, Cyprinus carpio , a similar suggestion was proposed as melatonin was shown to inhibit DA release in hypothalamus both in vivo and in vitro (109, 110).…”
Section: Discussionmentioning
confidence: 80%
“…However, an earlier study in the same species reported that high melatonin doses did not affect DA turnover in the hypothalamus (106). In rainbow trout, melatonin inferred a decrease in the hypothalamic‐pituitary DA turnover (107), a supposed step by which melatonin modulated LH secretion, as indicated in a previous study (108). In carp, Cyprinus carpio , a similar suggestion was proposed as melatonin was shown to inhibit DA release in hypothalamus both in vivo and in vitro (109, 110).…”
Section: Discussionmentioning
confidence: 80%
“…Keeping in mind that feeding is stimulated by NE and reduced by DA in goldfish [30,51], melatonin could probably reduce feeding and body weight by inhibiting noradrenergic activity and/or stimulating dopaminergic activity in fish hypothalamus. Herna´ndez-Rauda et al [52] found that a single melatonin injection reduces dopaminergic metabolism in hypothalamus of the rainbow trout, but feeding behavior was not evaluated. Nevertheless, it cannot be discounted that the reduction of DOPAC clearance may also contribute to the DOPAC increase found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Hernández‐Rauda et al. [52] found that a single melatonin injection reduces dopaminergic metabolism in hypothalamus of the rainbow trout, but feeding behavior was not evaluated. Nevertheless, it cannot be discounted that the reduction of DOPAC clearance may also contribute to the DOPAC increase found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study on the same species, however, reported that high melatonin doses did not affect hypothalamic DA turnover (Senthilkumaran & Joy, 1995). In O. mykiss , melatonin induced a fall in the hypothalamic‐pituitary DA turnover (Hernandez‐Rauda et al , 2000). As proposed in a previous study, by this negative effect, melatonin would modulate LH secretion (Saligaut et al , 1998).…”
Section: Regulation Of Dopaminergic Inhibitionmentioning
confidence: 99%